Implikasi Mata Kuliah Psikoneurososiolinguistik (Psikolinguistik, Neurolinguistik dan Sosiolinguistik) Terhadap Kompetensi Public Speaking - Bachtiar, Anis; Arif, Rozaqul; Udin, Muhammad Diak; Kasyfillah, Muhammad Haidarsyah (Jurnal Ilmu Komunikasi, 2023)
The researcher aims to explore whether linguistics courses (psycholinguistics, neurolinguistics, and sociolinguistics) have a positive impact on improving the public speaking competence of students in the Islamic Communication and Broadcasting Study Programme. To obtain answers to these questions, researchers used a quantitative approach, with field data collection and statistical analysis using the T-test. The result of this study is that before getting psychoneurolinguistic course learning, the average public speaking competence of trainees with 62 subjects is 49.1290. Meanwhile, after getting psychoneurolinguistic course learning, the average public speaking competence of 6th semester students of Islamic Communication and Broadcasting study programme increased to 62.3226. The significance value of -19.431 = 0.000 <0.05, indicating a significant difference in the public speaking competence of psychoneurolinguistic learning participants between before and after being given learning.